Copper‐Bismuth Bimetallic Microspheres for Selective Electrocatalytic Reduction of CO2 to Formate. Issue 5 (28th March 2019) - Jia, Lin; Yang, Hui; Deng, Jun; Chen, Junmei; Zhou, Yuan; Ding, Pan; Li, Leigang; Han, Na; Li, Yanguang
Summary of main observation and conclusion: Electrocatalytic carbon dioxide reduction holds great promise for reducing the atmospheric CO2 level and alleviating the energy crisis. High‐performance electrocatalysts are often required in order to lower the high overpotential and expedite the sluggish reaction kinetics of CO2 electroreduction. Copper is a promising candidate metal. However, it usually suffers from the issues of poor stability and low product selectivity. In this work, bimetallic Cu‐Bi is obtained by reducing the microspherical copper bismuthate (CuBi2 O4 ) for selectively catalyzing the CO2 reduction to formate (HCOO – ). The bimetallic Cu‐Bi electrocatalyst exhibits high activity and selectivity with the Faradic efficiency over 90% in a wide potential window. A maximum Faradaic efficiency of 95% is obtained at –0.93 V versus reversible hydrogen electrode. Furthermore, the catalyst shows high stability over 6 h with Faradaic efficiency of 95%. This study provides an important clue in designing new functional materials for CO2 electroreduction with high activity and selectivity. Abstract : Bimetallic Cu‐Bi CO2 RR electrocatalysts were prepared via the cathodic conversion of hierarchical CuBi2 O4 microspheres. They enabled the high‐performance electrocatalytic reduction of CO2 to formate with large current density, excellent selectivity, and sufficient durability.